Family graveyards form underappreciated local plant diversity hotspots in China's agricultural landscapes - Cheng Gong (Nature Portfolio, 2021)
Abstract In the intensively farmed, homogenous agricultural landscape of the North China Plain, family graveyards form distinct cultural landscape features. In addition to their cultural value, these graveyards represent semi-natural habitat islands whose potential roles in biodiversity conservation and ecological functioning has remained poorly understood. In this study, we investigated plant species richness on 199 family graveyards of different ages and sizes. In accordance with biogeography theory, both overall and insect-pollinated plant species richness increased with area and age of graveyards. Even small graveyards show a strong potential for conserving local plant richness, and a mosaic of both large and small family graveyards could play an important role in the conservation of farmland biodiversity and related ecosystem functions. The launch of agri-environmental measures that conserve and create semi-natural habitats, in turn benefitting agricultural biodiversity and ecological functioning, has proven difficult in China due to the shortage of dispensable arable land. Given the great value of family graveyards as semi-natural habitats reflected in our study, we propose to focus preliminary efforts on conserving these landscape features as existing, widespread and culturally important semi-natural habitat islands. This would represent an effective, complementary policy to a subsequent re-establishment of other semi-natural habitats for the conservation of biodiversity and ecological functioning in agricultural landscapes.